PERLINDUNGAN HUKUM TERHADAP NOTARIS PENERIMA PROTOKOL DALAM HAL TERJADI PELANGGARAN AKTA NOTARIS OLEH NOTARIS PEMBERI PROTOKOL YANG TELAH MENINGGAL - Trisnawati, Melita; Suteki, Suteki (Magister Kenotariatan Universitas Diponegoro, 2019)
The notary public as the general official has the authority to make authentic deed in accordance with the norms, the values and the provisions of the applicable legislation so that the law can work in the community. Every deed made by a notary must stored in a notary protocol, and the protocol shall be transferred in the event of a notary passing away. But the problem is when a notary has passed away and his protocol is transferred to another notary, then a dispute arises related to the deed. Notary recipient of the protocol will still be called for questioning if there is a problem related to the protocol that is in his control, because it is one of the responsibility of the recipient of notary protocol. This is where the role of MKN appears to provide protection in the form of inspection or investigation permits by the authorities. And the role of MPD and INI in preventing the occurrence of violations in the deed by the notary in the form of guidance to all members of the notary.Â Keywords : Notary Protocol, Original Of The Deed, Legal ProtectionÂ AbstrakPada hakekatnya notaris sebagai pejabat umum memiliki kewenangan untuk membuat akta otentik sesuai dengan norma-norma, nilai-nilai dan ketentuan peraturan perundang-undangan yang berlaku sehingga hukum dapat bekerja dalam masyarakat.. Setiap akta yang dibuat oleh notaris wajib disimpan dalam protokol notaris, dan protokol wajib dialihkan dalam hal notaris meninggal dunia. Namun yang menjadi persoalan adalah ketika seorang notaris telah meninggal dunia dan protokolnya dialihkan kepada notaris lain, kemudian muncul sengketa yang berkaitan dengan akta tersebut. Notaris penerima protokol tetap akan dipanggil untuk diminta keterangan apabila terdapat permasalahan terkait protokol yang ada dalam penguasaannya, karena merupakan salahsatu tanggungjawab penerima protokol notaris. Disinilah muncul peranan MKN untuk memberikan perlindungan berupa ijin pemeriksaan ataupun penyidikan oleh pihak yang berwenang. Serta adanya peranan MPD dan INI dalam mencegah terjadinya pelanggaran dalam pembuatan akta oleh notaris berupa pengayoman kepada seluruh anggota notaris. Kata kunci : Protokol Notaris, Minuta Akta Notaris, Perlindungan Hukum